Design and development of an industrial firefighting rover. (2021) - Manikandan, R.; Subash, K.; Joshua sujith, T.; Jayasuriyan, R.; Jerendran, J.; Rajpradeesh, T.; Rajesh, S.
Abstract: In this paper, the work is to make a firefighting rover that helps while salvaging activity. With the assistance of robot control through a remote framework incorporated with the RF module. Vision and its control are done in the versatile application and the control is unmistakably on the premise of remote transmission. It contains mechanical parts like dc engine, servo engine, and chain sprocket gear framework. With this development is accomplished and fire quenching is done under a specific stream rate that will be accomplished with the assistance of situating the spout and force gracefully with a 12v battery. The fire is an exothermic reaction and it's caused by a self-sustaining chemical reaction between fuel, oxygen, and heat. The consequence of fire accidents like fatality rate and burn injuries are very high in industries where especially the flammable materials are used. So, this firefighting rover is used to reduce the consequence and severity of fire mishaps, protect the employees against fire, and improve occupational health and safety.